The use of common property resources: A dynamic model - Michele Moretto; Paolo Rosato (Fondazione Eni Enrico Mattei (FEEM), 2002)
The government of common agricultural and forestry land is a topic that is currently enjoying a revival of interest. Many local communities have shown the ability to pursue sustainable use of natural resources thanks to their self-governed authorities. In this context the relationship between public and private interest which is established in use of the resource is a fairly controversial. The paper proposes a dynamic model to analyse the behaviour of a user of a common property resource in a "real option" framework, where the value of the right to use the resource is affected by: 1) uncertainty on the future amount of the resource; 2) entry and exit costs and 3) the number of users competitors.
Keywords: 330; Common property resources; option value; uncertainty; Gemeingüter; Dynamisches Modell; Theorie; Realoptionsansatz